STUDENTS’ PERCEPTIONS TOWARDS CODE-SWITCHING USES IN ENGLISH CLASS - Shalihah, Fadhilah A.; Noni, Nurdin; Aeni, Nur (Universitas Negeri Makassar, 2025)
Code-switching, the practice of alternating between languages in communication, is a common feature of multilingual English classrooms. This article examines students’ perceptions of teachers’ code-switching in an Indonesian high school English class and explores the teacher’s reasons for utilizing this practice. Drawing on a descriptive qualitative study at SMAN 1 Takalar with classroom observations and interviews of one teacher and five Grade 10 students, the findings indicate that students generally perceive code-switching positively. They report that the teacher’s strategic switches from English to Indonesian enhance their comprehension of complex material, reduce anxiety, and encourage participation. The teacher employs code-switching intentionally to clarify difficult vocabulary, explain abstract concepts, manage classroom interactions, and ensure inclusive understanding for students of diverse linguistic backgrounds. While both students and the teacher acknowledge the pedagogical benefits of code-switching, they also recognize the importance of not over-relying on the first language so as not to impede English immersion. A balanced, judicious use of code-switching is recommended. These findings underscore the pedagogical value of code-switching as a scaffolding tool in EFL classrooms and highlight the need to consider student perspectives in developing effective bilingual teaching strategies.